Ancient Greece : from the Mycenaean palaces to the age of Homer - Deger-Jalkotzy, Sigrid, 1940-; Lemos, I. S. (Irene S.) (Edinburgh : Edinburgh University Press, 2006)
The period between the collapse of the Mycenaean civilization around 1200 BC and the dawning of the classical era four and half centuries later is widely known as the Dark Age of Greece, not least in the eponymous history by A.M. Snodgrass published by EUP in 1971, and reissued by the Press in 2000. In January 2003 distinguished scholars from all over the world gathered in Edinburgh to re-examine old and new evidence on the period. The subjects of their papers were chosen in advance by the editors so that taken together they would cover the field. This book, based on thirty-three of the presentations, will constitute the most fundamental reinterpretation of the period for 30 years. The authors take issue with the idea of a Greek Dark Age and everything it implies for the understanding of Greek history, culture and society. They argue that the period is characterised as much by continuity as disruption and that the evidence from every source shows a progression from Mycenaean kingship to the conception of aristocratic nobility in the Archaic period. The volume is divided into six parts dealing with political and social structures; questions of continuity and transformation; international and inter-regional relations; religion and hero cult; Homeric epics and heroic poetry; and the archaeology of the Greek regions. Copiously illustrated and with a collated bibliography, itself a valuable resource, this book is likely to be the essential and basic source of reference on the later phases of the Mycenaean and the Early Greek Iron Ages for many years.
1. The formation of the Mycenaean palace / James C. Wright -- 2. Wanaks and related power terms in Mycenaean and later Greek / Thomas G. Palaima -- 3. Mycenaean palatial administration / Cynthia W. Shelmerdine -- 4. The subjects of the wanax : aspects of Mycenaean social structure / John T. Killen -- 5. [Anax] and [Basileys] in the Homeric poems / Pierre Carlier -- 6. Kin-groups in the Homeric epics (summary) / Walter Donlan -- 7. The Mycenaean heritage of Early Iron Age Greece / Oliver Dickinson -- 8. Coming to terms with the past : ideology and power in Late Helladic IIIC / Joseph Maran -- 9. Late Mycenaean warrior tombs / Sigrid Deger-Jalkotzy -- 10. The archaeology of basileis / Alexander Mazarakis Ainian -- 11. From Late Bronze Age to Early Iron Age copper metallurgy in mainland Greece and offshore Aegean Islands / Maria Kayafa -- 12. Ethne in the Peloponnese and Central Greece / Catherine Morgan -- 13. Gift exchange : modern theories and ancient attitudes / Beate Wagner-Hasel -- 14. Basileis at sea : elites and external contacts in the Euboean Gulf region from the end of the Bronze Age to the beginning of the Iron Age / Jan Paul Crielaard -- 15. Aspects of the 'Italian connection' / David Ridgway -- 16. From the Mycenaean qa-si-re-u to the Cypriote pa-si-le-wo-se : the basileus in the kingdoms of Cyprus / Maria Iacovou -- 17. Phoenicians in Crete / Nicholaos Chr. Stampolidis and Antonios Kotsonas -- 18. From kings to demigods : epic heroes and social change c. 750-600 B.C. / Hans van Wees -- 19. Religion, basileis and heroes / Carla Antonaccio -- 20. Cult activity on Crete in the early dark age : changes, continuities and the development of a 'Greek' cult system / Anna Lucia D'Agata -- 21. The rise and descent of the language of the Homeric poems / Michael Meier-Brugger -- 22. Homer and oral poetry / Edzard Visser -- 23. Some remarks on the semantics of [Anax] in Homer / Martin Schmidt -- 24. Historical approaches to Homer / Kurt A. Raaflaub -- 25. The palace of Iolkos and its end / Vassiliki Adrimi-Sismani -- 26. Early Iron Age elite burials in East Lokris / Fanouria Dakoronia -- 27. Athens and Lefkandi : a tale of two sites / Irene S. Lemos -- 28. The Early Iron Age in the Argolid : some new aspects / Alkestis Papadimitriou -- 29. The world of Telemachus : western Greece 1200-700 B.C. / Birgitta Eder -- 30. Knossos in Early Greek times / J.N. Coldstream -- 31. Praisos : political evolution and ethnic identity in eastern Crete c. 1400-300 B.C. / James Whitley -- 32. The gilded cage? : settlement and socioeconomic change after 1200 B.C. : a comparison of Crete and other Aegean regions / Saro Wallace -- 33. Homeric Cyprus / Vassos Karageorghis.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Iron age -- Greece -- Congresses; Greece -- History -- Geometric period, ca. 900-700 B.C. -- Congresses; Greece -- Civilization -- To 146 B.C. -- Congresses; Greece -- Civilization -- Congresses; Greece -- Antiquities -- Congresses; Âge du fer -- Grèce -- Congrès.; Grèce -- Antiquités -- Congrès.; Grèce -- Civilisation -- Jusqu'à 146 av. J.-C. -- Congrès.; Grèce -- Histoire -- ca 900-700 av. J.-C. (Époque géométrique) -- Congrès.; Grèce -- Civilisation -- Congrès.; HISTORY -- Ancient; HISTORY -- Ancient -- Greece; Antiquities; Civilization; Iron age; Greece; Griekse oudheid; To 146 B.C.; Congress; proceedings (reports); Conference papers and proceedings; History; Conference papers and proceedings; Actes de congrès.